Inequality, chronic undernutrition, maternity, and diabetes mellitus as the determinant of anemia among ever-married women in Bangladesh - G. M. Rabiul Islam (BMC, 2021)
Abstract Background Anemia is a public health concern at a global level. This study aims to delineate the association between household economic inequalities, and anemia among reproductive age group women in Bangladesh, along with other confounders. Methods A cross-sectional population sample from Bangladesh Demographic and health survey data comprising of 5920 reproductive age group women aged between 15 and 49 years was used in this study. The analyses were performed through the application of proportional odds into four models (viz., Model:1 socio-economic, Model:2 socio-demographic factors, Model 3: diabetics and maternity statis, Model 4: nutritional status.) Results The respondents from low and medium socioeconomic status (SES) households vs. richest households were 1.90 (95% CI, 1.65,2.17; p < .01) and 1.41 (95% CI, 1.12,1.78; p < .01) times more likely to suffer from anemia (Model 1). From the model 2 it appears that he likelihood of being anemic reduces for the low and medium SES groups vs. high SES group when sociodemographic variables are added (OR, 1.69, 95% CI, 1.43,1.99 and OR, 1.35, 95% CI, .07,1.70; p < 0.01, respectively). Model 3 evident that after adding the variables of diabetes and maternity status, the association between having anemia belonging to low and medium SES vs. high SES becomes weaker (OR1.36, 95% CI,0.85,2.15 and OR, 1.15, 95% CI, 0.6,2.19; p > .05, respectively). Moreover, the strength of the association between anemia and the subjects with pregnant vs. the subjects without these (OR: 1.7 (1.12, 4.02; p < 0.05) 1.47(0.11,3.399; p < 0.05) conditions was reduced after factoring body mass index (BMI, model 4). Besides, thin women (MBI < 18.50 Kg/m2) shows significantly become more likely to be anemic in comparison to women of normal BMI (OR:1.34, .92,1.96; p < 0.05) (model 4). Conclusions BMI, pregnancy, and diabetes mellitus were observed to be significantly associated with anemia, and the strength of the association was low with anemia and socioeconomic inequality.